2020
DOI: 10.1002/sd.2138
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sustainability reporting quality on the value relevance of corporate sustainability performance

Abstract: The value relevance of corporate sustainability performance (CSP) has been studied from different theoretical perspectives, yielding inconclusive evidence. Therefore, it is imperative to revisit corporate sustainability performance relevance for investors. This study explores the value relevance of corporate sustainability performance by studying the impact that the quality of sustainability reporting has on it. It employed the panel data of 247 firms from 2012 to 2016 for the best 30 green capital markets ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 87 publications
(130 reference statements)
2
31
1
3
Order By: Relevance
“…Despite the introduction of new regulatory requirements, the quality of sustainability reporting continued to improve, according to the findings of the study. Jadoon et al (2021) assessed the impact of sustainability reporting quality on sustainable corporate performance information content using data from 247 enterprises in 21 countries and the Green Economic Growth Index. The findings of the regression analysis revealed that the information content of sustainability performance derived from economic, social, and corporate governance components.…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the introduction of new regulatory requirements, the quality of sustainability reporting continued to improve, according to the findings of the study. Jadoon et al (2021) assessed the impact of sustainability reporting quality on sustainable corporate performance information content using data from 247 enterprises in 21 countries and the Green Economic Growth Index. The findings of the regression analysis revealed that the information content of sustainability performance derived from economic, social, and corporate governance components.…”
Section: Research Backgroundmentioning
confidence: 99%
“…As a result, nonfinancial research's informative substance focuses more on corporate sustainability performance and its dimensions (Aureli et al, 2020). This hypothesis includes quantitative and qualitative criteria as a major component in understanding stock price movements at the same time (Jadoon et al, 2021).…”
Section: Value Relevancementioning
confidence: 99%
“…Communicating with stakeholders should allow organisations to identify key sustainability issues that need to be addressed in strategic sustainability management and that should be at the core of sustainability reporting. In this way, organisations can effectively be accountable for their sustainability initiatives and produce higher quality sustainability reports, thus contributing to the value relevance of sustainability reporting sought by investors (AA1000, 2015; Jadoon et al, 2021). Some scholars, like Rensburg and de Beer (2011), insist that the entire stakeholder engagement process boils down to just plain good governance.…”
Section: The Benefits Of Stakeholder Engagementmentioning
confidence: 99%
“…There is as yet no consensus on theoretical propositions on corporate behaviour and propensity towards corporate sustainability performance (CSP) and corporate sustainability reporting (CSR) (Belal & Roberts, 2010;Deegan, 2002;Gray, Adams, & Owen, 2014;Gray, Kouhy, & Lavers, 1995;Gray, Owen, & Adams, 2009). Consequently, CSP/CSR has been studied from different theoretical perspectives, with conflicting or inconclusive evidence (See: (Jadoon, Ali, Ayub, Tahir, & Mumtaz, 2020)). Deegan (2002) was categorical about the absence of "an accepted theory for social and environmental accounting, [and] there is much variation in the theoretical perspectives being adopted".…”
Section: Theoretical Literaturementioning
confidence: 99%